PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBASIS VIDEO ANIMASI POWTOON DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA - insiano, dewi angraini; Alda Rahmadayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this research is the low mathematics learning outcomes of SDN 6 Tambun students, especially in the fraction aspect. To address this issue, the author conducted a study by implementing the Problem Based Learning (PBL) model using Powtoon animated videos in the learning process. The objectives of this study are (1) to determine the implementation of the Problem Based Learning (PBL) model based on Powtoon animated video media in teaching mathematics to second-grade students at SDN 6 Tambun, (2) to assess the mathematics learning outcomes of first-grade students at SDN 6 Tambun, and (3) to analyze whether there is an effect of implementing the Problem Based Learning (PBL) model using Powtoon animated videos on the mathematics learning outcomes of second-grade students at SDN 6 Tambun. This research employs a quantitative pre-experimental design (one-group pretest-posttest design). The study uses observation sheets and learning outcome tests as instruments, with a research sample of 19 students. The sample was selected using a purposive sampling technique. Data analysis was performed using the Paired Sample t-test. The results of this study indicate a probability value of 0.00, which is <0.025, leading to the conclusion that Ho is rejected and Ha is accepted. The positive implication of applying this model with integrated media is that teachers can consider incorporating technology and multimedia into their teaching strategies to enhance student engagement and understanding. Keywords: Problem Based Learning (PBL), Powtoon, Learning Outcomes